2003
DOI: 10.1046/j.1468-2982.2003.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Patients with Cervicogenic Headache

Abstract: Cervicogenic headache (CH) is a syndrome which is postulated to originate from nociceptive structures in the neck or head. The anatomical neck or head structures that are responsible for the pain in CH have not been clearly identified, but the pain in these patients probably originates from the structures of the cervical spine. In this study, cervical MRI were studied in 22 patients with cervicogenic headache and 20 control patients who did not have any disease which may effect the bone and muscle structures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 14 publications
1
22
0
2
Order By: Relevance
“…One cross-sectional phase 1 study compared MRI images of the cervical spine in patients with cervicogenic headache (n = 22) to MRIs of asymptomatic controls (n = 20). 95 Findings of bulging cervical disc were found in 45% both in patients and controls. Other common degenerative findings were no more frequently found in patients compared with controls (P N 0.05).…”
Section: Mri In Asymptomatic Individuals and Patients Withmentioning
confidence: 96%
“…One cross-sectional phase 1 study compared MRI images of the cervical spine in patients with cervicogenic headache (n = 22) to MRIs of asymptomatic controls (n = 20). 95 Findings of bulging cervical disc were found in 45% both in patients and controls. Other common degenerative findings were no more frequently found in patients compared with controls (P N 0.05).…”
Section: Mri In Asymptomatic Individuals and Patients Withmentioning
confidence: 96%
“…Neuroimaging does not serve as a reliable method for CEH diagnosis. MRI abnormalities in CEH do not differ from controls [28]. There is no biomarker for the diagnosis of CEH [29], although a lack in calcitonin generelated peptide increase in CEH, pointing to a fundamental difference in migraine, has been suggested [30].…”
Section: The Borderland Between Ceh Migraine and Tthmentioning
confidence: 90%
“…28 Radiologic studies of the spine may be helpful in assessing the degree of cervical facet joint degenerative changes, odontoid structure and stability, spinal 29 Cervical disc bulging, which was the primary focus of the study, was reported equally in both groups (45.5% versus 45.0%, respectively). Unfortunately, this study did not include cervical facet evaluation.…”
Section: Evaluation Of Cervicogenic Headachementioning
confidence: 99%